The Influence of Asmaul Husna Gamification on the Character of Madrasah Ibtidaiyah students - Feri Riski Dinata; Akla; Ahmad Zumaro; Ahmad Muzakki; Ali Kuswadi; Finan Akhsani Taqwim (Universitas Islam Negeri (UIN) Salatiga, 2026)
Objectives: This research aims to: 1) identify the elements of Asmaul Husna gamification; 2) explore the implementation of Asmaul Husna gamification in Islamic learning; and 3) examine the influence of Asmaul Husna gamification on the character development of Madrasah Ibtidaiyah (Islamic Primary School) students. Method: A quantitative quasi-experimental design with a pretest–posttest control group was employed. Forty students were divided into experimental and control groups. The experimental group received structured character education integrating gamification elements aligned with Asmaul Husna values, while the control group experienced conventional, memorization-based instruction. Data were collected using validated optimism and self-control scales and analyzed using ANCOVA to control for baseline differences. Results: The research reveals that: 1) the core elements of Asmaul Husna gamification include points, levels, badges, challenges, and feedback that integrate Islamic spiritual values; 2) the implementation follows a five-stage framework consisting of orientation, challenges, rewards, reflection, and progression; and 3) Asmaul Husna gamification significantly improves optimism and self-control in Madrasah Ibtidaiyah students. Theoretical Contribution: This research conceptualizes Islamic educational media by synthesizing Self-Determination Theory, positive psychology, self-regulation theory, and the Islamic concept of tazkiyatun nafs into an integrated educational framework. Implication: Asmaul Husna gamification offers a spiritually oriented educational tool to strengthen character development in Islamic primary school students.